Modular plants for combined biomass-based production of electricity and synthetic liquid fuel - E. A. Tyurina; A. S. Mednikov; P. Yu. Elsukov (Известия высших учебных заведений: Проблемы энергетики, 2020)
The high costs of qualified liquid fuels in remote areas of Siberia and the Far East, as well as significant stocks of wood biomass in these areas determine the relevance of the presented studies. The integrated processing of woody biomass into synthetic liquid fuel and electricity will increase the energy and economic efficiency of processing technological waste, as well as improve the environmental situation in these areas. The aim of the work is technical and economic optimization of parameters modular installations of the combined production of electricity and methanol from woody biomass. The article presents an analysis of previously performed work on the topic of research and, based on them, selected one of the most effective ways to process wood biomass - oxidative conversion of this raw material to produce gas enriched in hydrogen and carbon oxides, synthesis of qualified liquid fuels and generating electricity when burning purge gas synthesis process. The technological scheme of modular plants for combined biomass-based production of electricity and synthetic liquid fuel, its mathematical model of its elements and the scheme as a whole are given. On the basis of the selected methods, optimization studies of the operation of a modular energy technology installation were carried out. Analysis of the results showed that the combined production of electricity and methanol based on biomass increases the thermal efficiency of the process by 12% and reduces investment by 15-20% compared with separate production. With an internal rate of return of capital of 15%, the cost of methanol from biomass will be 275-317 dollars per ton. At such a cost, methanol can compete with both boiler-furnace and motor fuels in the eastern regions of Russia.